Biophysical Properties of Australia Antigen - Gerin, J. L. (1969)
Biophysical studies with Australia complement-fixing (CF) antigen showed it to be a particle with a buoyant density of 1.20 g/cm(3) in CsCl, a sedimentation coefficient of 110, and an average diameter of 25 nm. The CF antigen was not inactivated by ether, 1% deoxycholate, 1% Tween 80 or overnight heating at 56 C. The antigen was unstable when treated with 1% sodium dodecyl sulfate. A procedure is described for the isolation and partial purification of Australia antigen from serum by using isopycnic banding and rate separation techniques. Treatment of the 1.20 g/cm(3) Australia antigen with 1% Tween 80 yielded a minor peak of CF activity with a buoyant density of 1.39 g/cm(3) in CsCl.